Assessing tourists' preferences for conservation of large carnivores in the Italian Alps using a discrete choice experiment. Issue 7 (7th June 2022) - Notaro, Sandra; Grilli, Gianluca
Abstract : A study on tourists' preferences for wildlife conservation in the Italian Alps using a choice experiment is presented. The study focuses on wolves, lynx and salamanders, which are in danger of extinction. Welfare analysis suggests that WTP for varying sizes of animal population increases up to 45–55 animals and then decreases. This indicates that tourists are willing to financially contribute to an increase in the number of animals, but they do not want too many individuals, probably due to the impacts that large populations of carnivores may have. Estimated consumer surplus confirms a larger positive welfare change for the scenario with 50 animals. A population of 50 animals is considered a viable population for the survival of wolves and lynx; therefore results indicate that tourists are willing to contribute for sustainable wolf and lynx conservation. The analysis also indicates that the places of residence and where respondents grew up influence preferences.